A utilização da terapia de sandplay em crianças que apresentam sintomas de Transtorno de Oposição Desafiante (TOD) e Transtorno de Conduta (TC): um estudo quantitativo e compreensivo - Chalfon, Mariana S. Taliba (2020)
Epidemiological data indicate that Oppositional Defiant Disorder (ODD) and/or Conduct Disorder (CD) in childhood are predictors of mental disorders in adolescence and adulthood. Sandplay therapy (ST) is a nonverbal and expressive method based on Analytical Psychology. The study aimed at verifying the efficiency of ST for treatment of children with symptoms of ODD and/or CD; observing whether the improvement was sustained for three months; verifying the emerging themes in the ST and their evolution, considering the initial and final phase of the process. The research employed a mixed methodology with statistical analysis of CBCL/6-18 results. The instruments used were: Strengths and Difficulties Questionaire - parental version (SDQ), Abbreviated Weschler Intelligence Scale (WASI) and Child Behavior Checklist for ages 6-18 (CBCL/6-18). The intervention consisted of twelve weekly sessions of ST lasting 40 minutes. In each session, a scene was produced by the participant. Participants were forty-one children of both sexes, aged between 6 years and 11 years and 11 months, who were attending a Child and Adolescent Center in São Paulo city. Two groups were randomly formed: Experimental Group 1 (GE1), with 21 participants, and Control Group (CG), with 20 participants. The children from GE1 underwent the intervention and the children from the CG waited in line for three months. After the intervention for GE1 and the waiting period for GC, the CBCL/6-18 was applied again. Waiting children who still met inclusion criteria formed GE2 and then started TS. Three months after the end of the intervention, follow-up was performed for GE1 and GE2, which constituted the GETOTAL in the statistical analysis. The analysis between GE1 and CG showed improvement of symptoms in the following domains: Externalizing, Rule Breaking Behavior, Aggressive Behavior, Oppositional Defiant Problems, and Conduct Problems, with varying effect sizes from weak to strong. The analysis of GETOTAL showed improvement of symptoms with strong effect size in all domains mentioned above, just after ST. Although CBCL/6-18 results indicate that behaviour improvement was not sustained after three months, results remained relatively stable, as no regression of symptoms to baseline occurred in any of the domains. Comparison of the results obtained before the beginning and three months after the end of the intervention indicates that there was a statistically significant reduction with moderate or strong effect size in all domains except Somatic Problems. Participants produced 432 scenes. The themes “conflict”, “threat” and “wound” were more frequent in the early phase and less frequent in the final phase of ST. The opposite occurred with the theme “care”. Thus, CBCL6/6-18 results and the observed evolution in themes throughout intervention sessions show the efficiency of ST in reducing symptoms in children with symptoms of TOD and CT